IFLA LRM’s contributions to RDA: a systematic literature review - Oliveira, Rhuan Henrique Alves de (2022)
The RDA Toolkit Restructure and Redesign (3R) Project, finished in December 2020, aimed to align the RDA standard with the IFLA Library Reference Model (IFLA LRM), a conceptual model of the bibliographic universe that consolidates the models of the FR Family. Therefore, this research seeks to ascertain the contributions and impact of the IFLA LRM to RDA. Therefore, a Systematic Literature Review (RSL) was carried out in order to identify the state of the art of the subject in the scientific literature. It was found that the category in which the implementation of the IFLA LRM by the RDA is most explicitly attested is ontological, concerning the formal representation of the universe of things that exist in a given domain, and thus, the IFLA LRM plays an intermediary role, enabling the increasing integration of bibliographic data in RDA into the larger universe of Semantic Web and Linked Data data.